Teacher learning in an online social networking website - Kamalodeen, Vimala (School of Education, UWI, St. Augustine, 2014)
This study was designed to explore teacher learning using an online intervention with in-service secondary teachers in Trinidad and Tobago. It has been argued that traditional teachers' professional development practices do not adequately meet the needs of today's practitioners and that new models of teacher learning need to be explored for in-service teachers. In addition, non-traditional learning spaces such as social networking sites are being currently debated for their use in education. In this paper, an online social networking site is considered as an alternative learning space, which is mediated through Web 2.0 tools and the Internet. Social constructivism provides a framework to understand teachers' participation on the site as they interact with colleagues and add content to the site. Data were collected directly from the site and analysed using a mixture of methods. Data consisted of digital text and mixed media such as pictures, videos, and hyperlinks. Findings indicated that teachers participated in activities across space and time, and preferred certain activities over others. They shared knowledge and opinions of their classrooms and schools, reflected on their practice, and connected with new people. Learning is concluded to have taken place through participation on the site. This study provides an avenue for further research on how teachers can experience a shift from traditional professional development
Keywords: Inservice teacher education; Secondary school teachers; Professional development; Online learning; Social networking service; Trinidad and Tobago